Multimedia-Based Interactive Mathematics Learning Application for Elementary Schools Using Fuzzy Logic Method - Chaeroen Niesa; Mutasar (Gameology and Multimedia Expert, 2026)
This research aims to develop a multimedia-based interactive mathematics learning application for elementary school students. The application was developed using Adobe Flash CS5 and is integrated with the Fuzzy Logic method to enhance learning interactivity. The content presented covers basic mathematical operations, including addition, subtraction, multiplication, and division, tailored for first to third-grade elementary school students. In addition to the learning materials, the application provides practice exercises to evaluate student comprehension. The utilization of multimedia in this application is expected to assist teachers in delivering material more engagingly and to facilitate students' understanding of mathematics lessons. The research results indicate that this interactive learning application can enhance students' learning interest, motivation, and comprehension of mathematics.